EFFICACY OF INTRA-ARTICULAR DEXMEDETOMIDINE FOR POSTOPERATIVE ANALGESIA IN ARTHROSCOPIC KNEE SURGERY (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction Post-operative pain is very common distressing symptom after any surgical procedure.Different drugs in different routes have been used for controlling post-arthroscopic pain.We have compared the efficacy of analgesic effect of plain ropivacaine versus ropivacaine with dexmedetomidine as an adjuvant when administered through the intra-articular route in arthroscopic knee surgery. Materials and Methods From June 2017 to June 2019 sixty patients undergoing elective knee arthroscopy were randomly assigned to two groups (n=30). Group R received 19 ml of 0.50% ropivacaine and 1 ml of isotonic saline (total volume 20 ml) intraarticularly. Group RD received 100 μg (1 ml) of dexmedetomidine added to 19 ml of 0.50% ropivacaine intra-articularly(total 20ml).Pain was assessed using visual analogue scale(VAS) and diclofenac sodium given as rescue analgesia when VAS>4.Time of first analgesia request and total dose of rescue analgesics used in 24 hours were calculated. Results VAS score were significantly lower in Group RD, time to first analgesic requirement was significantly greater in Group RD than in Group R and total dose of analgesics used in Group RD patients was significantly less compared to patients in Group R. Conclusion Dexmedetomidine, added as adjunct to ropivacaine in patients undergoing arthroscopic knee surgery, improves the quality and duration of postoperative analgesia.
Keywords: dexmedetomidine; ropivacaine; arthroscopic knee surgery; intra-articular injection